THE EFFECT OF GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY TO TAX AVOIDANCE - Indah Umiyati; Dewi Andriani (JASS (Journal of Accounting for Sustainable Society), 2023)
This study aims to determine the effect of good corporate governance, corporate social responsibility, and profitability on tax avoidance. The independent variables used are good corporate governance as proxied by independent commissioners, corporate social responsibility as proxied by CSR costs and profitability as proxied by return on assets (ROA). The dependent variable used is tax avoidance proxied by the cash effective tax rate (CETR). The sampling method used is purposive sampling method and obtained a sample of 10 companies so that there are 50 research samples. The data used is secondary data, namely the financial statements of the food and beverage sector companies in 2017-2021. In order to prove the hypothesis, multiple regression testing was carried out. The results show that independent commissioners have no effect on tax avoidance in food and beverage companies in Indonesia. The cost of CSR has a significant effect on the tax avoidance of food and beverage companies in Indonesia. Meanwhile, profitability does not affect the tax avoidance of food and beverage companies in Indonesia.